Analysis of the response of a roadway bridge under extreme flooding-related events: Scour and debris-loading. (15th March 2023) - Kosič, M.; Prendergast, L.J.; Anžlin, A.
Highlights: Detailed flood analysis of roadway bridge exposed to extreme events with scour and debris. Scour examination is performed in concurrence with hydrodynamic and debris loading. Ambient-vibration data is used for model calibration. Two types of soil-structure interaction modelling are considered and compared. Debris-induced amplification of scour is examined, and it is shown to increase the failure potential of the bridge. Abstract: Hydraulic actions on bridges are a leading cause of failure, especially due to the occurrence of scour erosion. Due to climate change, flooding and scour risks are exacerbating for bridges worldwide, leading to a significant stress burden on asset management agencies. Assessing structures for scour has received significant attention in recent years, however, there are few studies which investigate the influence of scour on the components of a bridge to understand how various elements interact. Moreover, the presence of debris loading, which can occur due to flooding causing debris to become lodged at structures, has not received significant attention. Debris can worsen scour conditions and increase hydraulic loading on a bridge. In this paper, an analysis of the response of various components of a roadway bridge when exposed to extreme flooding is conducted. The influence of scour and debris on hydraulic loading, internal forces, modal periods, and utilization ratios of various bridge components is ascertained. A numerical model is developed using OpenSees employing two different methods to model the soil-structure interaction. Results for several flooding scenarios show how the various bridge elements are influenced by variations in water height and velocity, scour depth, and presence of debris.